A concise review of common animal models for the study of limb regeneration. (2nd July 2016) - Farah, Zayd; Fan, Huimin; Liu, Zhongmin; He, Jia-Qiang
ABSTRACT: Correct selection of an appropriate animal mode to closely mimic human extremity diseases or to exhibit desirable phenotypes of limb regeneration is the first critical step for all scientists in biomedical and regenerative researches. The commonly-used animals in limb regeneration and repairing studies, such as axolotl, mice, and rats, are discussed in the review and other models including cockroaches, dogs, and horses are also mentioned. The review weighs the general advantages, disadvantages, and precedent uses of each model in the context of limb and peripheral injury and subsequent regeneration. We hope that this review can provide the reader an overview of each model, from which to select one for their specific purpose.